Improving The Mechanisms Of Forming Professional And Creative Skills In Preschool Students - Mamura Abdumuminovna Ismanova (Euro Asian Journal Publishing, 2024)
This article describes creativity, development of creative competence of students of preschool education, innovative activities of students, interactive education, innovative education and information and communication technologies, factors that develop students' creativity.
Keywords: students; creativity; ability; interactive methods